How commuting influences urban economies and the environment: A Commuting Satellite Account applied to the Lisbon Metropolitan Area - Ferreira, João Pedro da Rocha (2016)
PhD Thesis in Sustainable Energy Systems submitted to the Faculty of Sciences and Technology of the University of Coimbra